Modal Sosial Dalam Pengembangan Madu Kelulut Sebagai Komoditas Ekonomi Dan Pariwisata Di Kecamatan Lubuk Kabupaten Bangka Tengah - Luna Febriani; Putra Pratama Saputra (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2018)
Kelulut Honey is one of the new commodities in Lubuk Subdistrict and has been developed by many local people. The development of this honeyed honey indirectly affects the income sector for the community and also has an impact on the development of tourism in the village. This study aims to identify and analyze social capital that is used by the Lubuk Sub-district community in developing the commodity of honey honey. The research method used to conduct this study is a qualitative method that emphasizes the deepening of a meaning and phenomenon. In analyzing this research, the concept and theory of social capital will be used by Robert Putnam. The results of the study show that there is the use of social capital in the effort to develop honey honey as a sector of the community's income and tourism sector. Social capital used includes: trust, networks and norms of the local community, so that the optimal use of social capital makes honey honey as a commodity in Lubuk District.